Supramolecular gels for antimicrobial photodynamic therapy against E. coli and S. aureus - Kavya Anguluri; Bunty Sharma; Saman Bagherpour; Ana C. Calpena; Lyda Halbaut; David B. Amabilino; Gurpreet Kaur; Ganga Ram Chaudhary; Lluïsa Pérez-García (Photodiagnosis and Photodynamic Therapy)
Singlet oxygen (SO) reacts with organic molecules, for example in degrading environmental contaminants and causing toxicity to cells in photodynamic therapy (PDT). The relevance of SO in the environmental and biomedical domains has fuelled research towards improved methodologies for its efficient generation. In this paper, we report the use of a bis-imidazolium-based amphiphile that forms supramolecular gels in water-ethanol mixtures encapsulating SO generating chromophores. The gels comprise twisted fibres that incorporate one of four different porphyrins: 5,10,15,20-tetrakis(N-methyl-4-pyridinium)porphyrin tetraiodide (TPPP), 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP), 5,10,15,20-tetrakis(3-hydroxyphenyl)porphyrin (TPP-3OH) and 5,10,15,20-tetrakis(4-hydroxyphenyl)porphyrin (TPP-4OH). Rheological measurements confirmed viscoelastic properties characteristic of these types of supramolecular gels, suggesting their potential as effective local PDT delivery systems. Enhanced SO generation within the hydrogel matrix compared to the solution of the chromophores was observed in suspension in a spectrophotometer using uric acid as the molecular probe. The SO generation was also shown through antimicrobial PDT (aPDT) studies. The TPPP-containing gel showed the highest reduction in the colony forming unit (CFU) count, which is 94% against E. coli and 100% against S. aureus. These results indicate that the porphyrin gels based on a gemini amphiphile with a high level of SO production are of significant interest and have a lot of potential use in aPDT.